2019
DOI: 10.1111/cch.12692
|View full text |Cite
|
Sign up to set email alerts
|

The information needs of children having clinical procedures in hospital: Will it hurt? Will I feel scared? What can I do to stay calm?

Abstract: BackgroundChildren often have unmet information needs when attending hospital, and this can cause them anxiety and uncertainty. If children are prepared and informed about what will happen during a procedure, they tend to have a better experience. Finding out what children want to know before they attend hospital for procedures could provide significant benefits for children, their families, and healthcare professionals. This study set out to investigate children's perspectives of what information is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 61 publications
2
42
1
21
Order By: Relevance
“…The DTx platform provides information about a broad range of hospital procedures, environments, and professionals; this is important as children can often encounter many different experiences when visiting the hospital, which may not be addressed by current digital health education and preparation interventions that focus on one specific procedure, for example, admission for surgery [ 13 - 16 , 29 ], or are designed around one specific hospital setting [ 30 ]. These interventions are of value but may not address the questions and concerns children have about procedures identified in previous research [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The DTx platform provides information about a broad range of hospital procedures, environments, and professionals; this is important as children can often encounter many different experiences when visiting the hospital, which may not be addressed by current digital health education and preparation interventions that focus on one specific procedure, for example, admission for surgery [ 13 - 16 , 29 ], or are designed around one specific hospital setting [ 30 ]. These interventions are of value but may not address the questions and concerns children have about procedures identified in previous research [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DTx platform also includes several serious games with health themes. The DTx platform includes information about the procedure, environment and staff, and information on sensory aspects of a procedure (what a child may feel or experience) as well as information to help a child build‑coping strategies [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no standard for the preparation of children undergoing surgery or invasive procedures such as UDS. Through qualitative interviews with 106 children, Bray et al 23 found that “children construct an understanding of a planned procedure through actively scaffolding procedural, sensory, and self‐regulation information.” There are several formats for the delivery of this information, including displaying information in an instructional video, booklet or Internet‐based format, behavioral preparation strategies including coping/relaxation instruction, medical play, interventions by a child life specialist or some combination of these. Fortier et al 24 created an Internet‐based behavioral preparation program for children undergoing outpatient surgery, which led to reductions in preoperative anxiety.…”
Section: Discussionmentioning
confidence: 99%